Building Bridges to Better Bonds? Bridging and Bonding Capital Development Through On-Campus Club Participation among International and Domestic Student - Malette, Nicole; Ismailzai, Emily (Canadian Journal of Higher Education, 2020)
Helping international students create meaningful on-campus connections is a major part of higher education’s internationalization efforts. By focusing on the efforts made by both international and domestic students to develop a sense of belonging through on-campus organizations like clubs and sports, we have the opportunity to consider their active creation of bridging and bonding capital. Through structured interviews with 150 international Asian and domestic White and Asian students enrolled at one of the largest universities in Canada, this research demonstrates that ethnicity-based on-campus organizations play a key role in helping international students build bonding capital on campus. However, findings from this research also demonstrate that international and domestic student groups do not take part in the same on-campus organizations. Differences in participation and discriminatory attitudes held by domestic White students have the potential to inhibit bridging capital, limiting integration between student groups